Examining Macroeconomic Indicators And Their Reletionship With The Idx Composite Stock Index (IHSG) - Irwan, Muhammad; Mubaraq, Muhammad Raihan; Awwalunnisa, Nur (IQTISHADUNA, 2024)
This study looks at the effect of macroeconomics indicators, namely the BI rate, inflation, and exchange rates on the IDX composite stocks index (IHSG). The IDX composite index is one of the sources investors use to choose their investment strategy. Inflation, exchange rate, BI rate, and composite stock index are some of variables that comprise the sample used in this study, including 88 models from 2016 to 2022. Data analysis was conducted using the multiple regression method. Based on finding, money supply, inflation, and BI rate have no significant impact on IDX composite stock index, and the exchange rate positively influence IDX composite stock index. Additional analysis needs to be done by looking at other potential macroeconomic factors. Summarize the novelty of this paper. Briefly explain why no one else has adequately researched the question yet.